Pen-and-paper versus digital sketching in architectural design education. (September 2019) - Heidari, Parvin; Polatoğlu, Çiğdem
This study aimed to compare and evaluate the digital-based sketching versus conventional pen-and-paper sketching through conducting an experiment via protocol study in educational field. To this aim, the linkography analysis technique was used to obatin the related data from the protocol study. Linkography technique allows analyzing design as a system and is capable of tracing the design ideas and their connections; therefore, it facilitated the purposes of the current study. The results demonstrated that designers had a richer design process and more opportunities for generating ideas in the pen-and-paper sketching versus digital sketching. Furthermore, the designers' performance in the digital media with two-dimensional sketching software was more satisfactory than the digital session with three-dimensional sketching software. However, digital media encouraged designers to make more integration among the ideas.